Central irisin administration suppresses thyroid hormone production but increases energy consumption in rats. (1st May 2018) - Tekin, Suat; Erden, Yavuz; Ozyalin, Fatma; Onalan, Ebru Etem; Cigremis, Yilmaz; Colak, Cemil; Tekedereli, Ibrahim; Sandal, Suleyman
Highlights: Irisin infusion increased food intake in rats. Irisin infusion decreased the thyroid hormone levels, but increased the body temperature. Infusion of irisin increased UCP1 in adipose tissues and UCP3 mRNA levels in muscle tissue. Abstract: Irisin, which is secreted from the skeletal muscle in response to physical exercise and defined as a thermogenic peptide, may play an important role in energy metabolism. Thyroid hormones, which are one of the other influential factors on the metabolic status, increase heat production and are the main regulators of energy metabolism. This study was conducted to determine the possible effects of irisin administration on thyroid hormones. Forty adult male Wistar albino rats were used in the study. The rats were equally divided into 4 groups (n = 10). The brain infusion kit was implanted in the groups, and irisin (or solvent as control) was centrally administered to the rats via osmotic mini pumps for 7 days. During the experiment, food consumption, body weights, and body temperatures of the animals were recorded. Food intake was significantly increased in the groups treated with irisin (p < 0.05), but their body weights were not changed. Hypothalamic TRH gene expression, serum TSH, fT3, and fT4 levels were significantly lower in the groups treated with irisin as compared to the naive and control groups (p < 0.05). In addition, irisin increased UCP1 mRNA expression in white and brown adipose tissue and UCP3 mRNA expression in muscle tissue in rats and also raised their body temperature (p < 0.05). Consequently, although central irisin administration has inhibitory effects on the hypothalamic-pituitary-thyroid axis, it seems to be an important agent in the regulation of food intake and energy metabolism.